Spiritual practices of female cancer patients towards well-being in lives - A'dawiyah Ismail (Penerbit Universiti Kebangsaan Malaysia, 2019)
There are various types of cancer experienced by women, for example breast, ovarian colon and cervical. Female cancer patients would often be in grief and anxiousness thinking about the risks of the illness and in looking for the appropriate practices in treating their emotions as well as their physique. This paper examines the spiritual practices of 20 patients with cancer at the National Cancer Society Malaysia. The design of this study is quantitative. The data were descriptively analysed based on the frequency, percentage and mean. The findings of the study show that the respondents' spiritual practices are at a high level of mean such as giving charity (3.81), seeking forgiveness from Allah the Almighty (3.81), reciting the Quran and its translation (3.75) and remembrance of Allah (3.75). The spiritual practices performed by the cancer patients help to stabilise their emotions and reduce their physical pain. The spiritual practices also help them to persevere in facing life in a good way towards achieving well-being in their lives apart from continuing with the modern treatments as recommended by the doctors, as well as to be consistent in practising the spiritual practices as proposed by Islam in order to gain emotional and mental health remedies.